Pengaruh Lokasi Dan Price Discount Terhadap Keputusan Pembelian Pada CV. Super Com - Sabaruddin Chaniago (Jurnal Mahkota Bisnis (Makbis), 2022)
Satisfaction has an important meaning not only for consumers but also for companies in supporting their survival. The purpose of this study is to determine the effect of location and price discount on purchasing decisions. This type of research is quantitative. The population in the study is CV. Super Com, while the sampling technique uses accedental sampling. Collecting data using a questionnaire with a Likert scale. The results of data analysis show that location and price discount have a positive and significant effect on purchasing decisions. Furthermore, the value (R2) is 0.548 (54.8%). So it can be said that 54.8% of the variation in the dependent variable, namely location and price discount on the model, can explain the purchasing decision variables in CV. Perfect Com while the remaining 45.2% is influenced by other variables outside the model.